The complete chloroplast genome of Tianshan Snow Lotus (Saussurea involucrata), a famous traditional Chinese medicinal plant of the family Asteraceae. (4th March 2017) - Xie, Qing; Shen, Kang-Ning; Hao, Xiuying; Nam, Phan Nhut; Ngoc Hieu, Bui Thi; Chen, Ching-Hung; Zhu, Changqing; Lin, Yen-Chang; Hsiao, Chung-Der
Abtract: We decoded the complete chloroplast DNA (cpDNA) sequence of the Tianshan Snow Lotus ( Saussurea involucrata ), a famous traditional Chinese medicinal plant of the family Asteraceae, by using next-generation sequencing technology. The genome consists of 152 490 bp containing a pair of inverted repeats (IRs) of 25 202 bp, which was separated by a large single-copy region and a small single-copy region of 83 446 bp and 18 639 bp, respectively. The genic regions account for 57.7% of whole cpDNA, and the GC content of the cpDNA was 37.7%. The S. involucrata cpDNA encodes 114 unigenes (82 protein-coding genes, 4 rRNA genes, and 28 tRNA genes). There are eight protein-coding genes ( atpF, ndhA, ndhB, rpl2, rpoC1, rps16, clpP, and ycf3 ) and five tRNA genes ( trnA-UGC, trnI-GAU, trnK-UUU, trnL-UAA, and trnV-UAC ) containing introns. A phylogenetic analysis of the 11 complete cpDNA from Asteracease showed that S. involucrata is closely related to Centaurea diffusa (Diffuse Knapweed). The complete cpDNA of S. involucrata provides essential and important DNA molecular data for further phylogenetic and evolutionary analysis for Asteraceae.